Motion Design with Efficient Actuator Placement for Adaptive Structures that Perform Large Deformations - Sachse, Renate; Geiger, Florian; von Scheven, Malte; Bischoff, Manfred (Frontiers in Built Environment, 2021)
Adaptive structures have great potential to meet the growing demand for energy efficiency in buildings and engineering structures. While some structures adapt to varying loads by a small change in geometry, others need to perform an extensive change of shape to meet varying demands during service. In the latter case, it is important to predict suitable deformation paths that minimize control effort. This study is based on an existing motion design method to control a structure between two given geometric configurations through a deformation path that is optimal with respect to a measure of control efficiency. The motion design method is extended in this work with optimization procedures to obtain an optimal actuation system placement in order to control the structure using a predefined number of actuators. The actuation system might comprise internal or external actuators. The internal actuators are assumed to replace some of the elements of the structure. The external actuators are modeled as point forces that are applied to the structure nodes. Numerical examples are presented to show the potential for application of the motion design method to non-load-bearing structures.